An Improved Current Ripples Minimization Technique for Cascaded DC–DC Converter in DC Microgrid - Khadidja Khattab; Ahmed Safa; Abdelmadjid Gouichiche; Youcef Messlem; Djaffar Ould Abdeslam; Abdelilah Chibani (Electrica)
The distributed direct current (DC) power system relies heavily on the cascaded DC–DC converter that employs a common bus to connect multiple DC–DC converters. The first stage of the cascaded DC–DC converter is responsible for injecting power from a renewable source or a battery into the DC bus. Conversely, the second stage connects a load to the DC bus, creating a constant power load (CPL) that consumes constant power regardless of the supply voltage. This behavior often causes disturbances and instabilities, leading to unwanted oscillations that adversely impact the quality of the input current. To address this issue, this paper proposes an active current ripple-damping technique that extracts the fundamental of the inductor current. When combined with the super-twisting sliding mode control, this approach effectively mitigates input current ripples and enhances the stability of the CPL. The key to this approach is the sliding surface selection, which requires a cleaned inductor current from the second boost converter. Experimental results are provided to demonstrate the effectiveness of the proposed method.